3′ Splice Site Sequences of Spinal Muscular Atrophy Related SMN2 Pre-mRNA Include Enhancers for Nearby Exons - Sunghee Cho; Heegyum Moon; Tiing Jen Loh; Hyun Kyung Oh; Hey-Ran Kim; Myung-Geun Shin; D. Joshua Liao; Jianhua Zhou; Xuexiu Zheng; Haihong Shen (The Scientific World Journal)
Spinal muscular atrophy (SMA) is a human genetic disease which occurs because of the deletion or mutation of SMN1 gene. SMN1 gene encodes the SMN protein which plays a key role in spliceosome assembly. Although human patients contain SMN2, a duplicate of SMN1, splicing of SMN2 produces predominantly exon 7 skipped isoform. In order to understand the functions of splice site sequences on exon 7 and 8, we analyzed the effects of conserved splice site sequences on exon 7 skipping of SMN2 and SMN1 pre-mRNA. We show here that conserved 5′ splice site sequence of exon 7 promoted splicing of nearby exons and subsequently reduced splicing of distant exons. However, to our surprise, conserved 3′ splice site sequence of exon 7 and 8 did not promote splicing of nearby exons. By contrast, the mutation inhibited splicing of nearby exons and subsequently promoted splicing of distant exons. Our study shows that 3′ splice sites of exon 7 and 8 contain enhancer for their splice site selection, in addition to providing cleavage sites.